Shifting online: an exploratory study into PR consultants' attitude towards new media - Wolf, Katharina; Archer, Catherine (Australian and New Zealand Communication Association, 2011)
This study set out to explore the current usage and knowledge of new media as a public relations tool and channel amongst practicing public relations consultants in Australia. The research was motivated by a nationwide benchmarking study by de Bussy and Wolf (2009), which concluded that new media was an extremely low priority for Australian public relations practitioners. Taking into account the speed of change associated with new media adoption, the authors examone whether these findings are still true today. This study takes a qualitative approach, based on a critical analysis of semi-structured interviews with WA based Registered Consultancy Group (RCG) members of the Public Relations Institute of Australia (PRIA) (n=7). Findings suggest a cautious attitude towards the benefits of new media amongst RCG consultants. This is largely based on the assertion that the dynamics of basic communication principles and theories have not changed and that there is consequently no perceived pressure to move into the new media sphere half heartedly.